Synthesis, Phase Behavior and Computational Simulations of a Pyridyl-Based Liquid Crystal System - Fowzia S. Alamro (MDPI AG, 2021)
A homologous set of liquid crystalline materials (Tn) bearing Schiff base/ester linkages were prepared and investigated via experimental and theoretical techniques. Terminal flexible groups of different chain lengths were connected to the end of phenylbenzoate unit while the other end of molecules was attached to the heterocyclic pyridine moiety. The molecular structures of the designed molecules were evaluated by FT-IR, NMR spectroscopic analyses, whereas their mesomorphic properties were investigated by polarized optical microscopy (POM) and differential scanning calorimetry (DSC). They all exhibited dimorphic properties with the exception of the members having the shortest and longest terminal flexible chains (n = 6 and 16), which were monomorphic. The T16 derivative was further found possessing purely smectic A (SmA) mesophase while others have their lengths covered by nematic (N) phase. Moreover, the computational evaluation of the azomethine derivatives was carried out using a DFT approach. The polarity of the investigated derivatives was predicted to be appreciably sensitive to the size of the system. Furthermore, the Frontier molecular orbitals analysis revealed various distributions of electron clouds at HOMO and LUMO levels.